Persuasive Utterances in Selected Tourism Advertisements on Indonesia.Travel YouTube Channel - Siti Mardiyah; Sawirman (Andalas International Journal of Socio-Humanities, 2021)
This study aims to identify the mode of persuasion and persuasive strategies used in Indonesia.Travel YouTube Channel. Ten videos among 256 ones were selected as data sources. Data collection was done by the non-participant method. Based on the research, the speakers used 38 persuasive utterances. The modes of persuasion used are pathos and logos. The most dominant mode of persuasion is pathos, with a percentage of 92%. Furthermore, there are three persuasive strategies were found namely: 1) quasilogical was found in 3 utterances (8%), 2) presentational was found in 33 utterances (87%), and 3) repetition was found in 2 utterances (5%). The results showed that the most dominant presentational strategy was found with a percentage of 87%. Therefore, it can be concluded that pathos and presentational strategies are used when speakers want to persuade their listeners by targeting their feelings and emotions.